KEDUDUKAN PERATURAN NAGARI BERDASARKAN UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - Rita Adriani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Nagari regulations are stipulated by the village head after being discussed and agreed with the village consultative body as a legal and policy framework for administering village governance and village development. This is what will be discussed in this article, regarding the extent to which the position of Nagari Regulations is based on Law Number 6 of 2014 concerning Villages. The method used in this research is normative legal research. The results of the study concluded that the substance of the village regulation contained material on the implementation of village government authority and further elaboration of higher laws and regulations. The existence of the nagari regulations received a strong legal basis after the existence of the Village Regulations was again recognized as statutory regulations based on Law Number 6 of 2014 concerning Villages which specifically regulates Village Regulations. Nagari regulations that were formed in the context of carrying out village government functions, among others, have been regulated in Law no. 6 of 2014 concerning Villages, such as: draft Village Expenditure Revenue Budget (APBDes), Medium Term Development Plan (RPJM) and Village Government Work Plan (RKPD), establishment of Village Owned Enterprises (BUMDes). Keywords: Position, Nagari Regulations, Village Law.